MR Imaging of SCA3/MJD - Wan, Na; Chen, Zhao; Wan, Linlin; Tang, Beisha; Jiang, Hong (Frontiers in Neuroscience, 2020)
Spinocerebellar ataxia type 3/Machado-Joseph disease (SCA3/MJD) is a progressive autosomal dominantly inherited cerebellar ataxia characterized by the aggregation of polyglutamine-expanded protein within neuronal nuclei in the brain, which can lead to brain damage that precedes the onset of clinical manifestations. Magnetic resonance (MR) imaging techniques such as morphometric MRI, diffusion tensor imaging (DTI), functional magnetic resonance imaging (fMRI) and magnetic resonance spectroscopy (MRS) have gained increasing attention as noninvasive and quantitative methods for the assessment of structural and functional alterations in clinical SCA3/MJD patients as well as preclinical carriers. Morphometric MRI has demonstrated typical patterns of atrophy or volume loss in the cerebellum and brainstem with extensive lesions in some supratentorial areas. DTI has detected widespread microstructural alterations in brain white matter, which indicates disrupted brain anatomical connectivity. Task-related fMRI has presented unusual brain activation patterns within the cerebellum and some extracerebellar tissue reflecting decreased functional connectivity of these brain regions in SCA3/MJD subjects. MRS has revealed abnormal neurochemical profiles, such as the levels or ratios of N-acetyl aspartate (NAA), choline (Cho) and creatine (Cr), in both clinical cases and preclinical cases before the alterations in brain anatomical structure. Moreover, a number of studies have reported correlations of MR imaging alterations with clinical and genetic features. The utility of these MR imaging techniques can help to identify preclinical SCA3/MJD carriers, monitor disease progression, evaluate response to therapeutic interventions and illustrate the pathophysiological mechanisms underlying the occurrence, development and prognosis of SCA3/MJD.